Evaluation of quality of MBBS Biochemistry theory question papers of medical institutions in Maharashtra - Patke, Vinay; Dahake, Hemant; Kuyare, Sunil (International Journal of Research in Medical Sciences, 2017)
Background: In medical curricula, the assessment of cognitive domain of learning is through written theory examination. At present questions are prepared casually just before the examination and are not put through any quality check to assess reliability, validity, educational impact, and acceptability. Methods: This study was conducted to retrospectively review and evaluate question items in Biochemistry examination question paper, according to specified criteria with the intention to determine its quality and design. A total of 14 preliminary examination question papers were collected by request from medical colleges affiliated to Maharashtra University of Health Sciences, Nashik; to evaluate selection of topics, their weightage, cognitive level, difficulty level and types of MCQ, SAQ and LAQ items, as per prescribed structure and protocol of question setting. The data was compiled in Microsoft excel, and coefficient of variation was calculated for each parameter tested. Results: There was variation in the topic wise distribution of marks in relation to lecture hours and weightage assigned to each topic. In general, there was inconsistency and nonconformity with respect to the characteristics for maintaining quality. Inadequacy of testing higher cognitive levels and lack of case based and application type of questions was observed. Conclusions: The quality of question paper setting can be improved by introducing blue print in assessment system. The use of the blue print will ensure consistent high standard of question presentation, which will help students to understand the questions better and to answer them correctly.